Bilateral Acromioclavicular Septic Arthritis as an Initial Presentation of Streptococcus pneumoniae Endocarditis - Neda Hashemi-Sadraei; Rohan Gupta; Jorge D. Machicado; Rukma Govindu (Case Reports in Infectious Diseases)
Infective endocarditis (IE) is infrequently associated with septic arthritis. Moreover, septic arthritis of the acromioclavicular (AC) joint is rarely reported in the literature. We report a case of Streptococcus pneumoniae IE in a patient who presented with bilateral AC joint septic arthritis and we review the literature on the topic.